Encyclopedia of Life Sciences 2018
DOI: 10.1002/9780470015902.a0000939.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Animal Venoms: Origin, Diversity and Evolution

Abstract: Venomous animals and their venoms have intrigued mankind for millennia. Venoms are complex cocktails of chemically diverse components that disrupt the physiological functioning of the victim to aid the venom‐producing animal in defence and/or feeding. Despite evolving independently on at least 30 occasions in the animal kingdom, venom exhibits remarkable evolutionary convergence, both in composition and biochemical activity. Various factors, including geography, diet, predator pressure, evolutionary arms race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Studies on the venom systems of arachnids, snakes, and marine cone snails, among others, have revealed that venoms are typically complex composites of peptides, small molecules, pore-forming proteins, and enzymes that target the nervous and/or cardiovascular system to incapacitate prey or deter predators. Venom has evolved multiple times among animals [ 1 , 2 , 3 ], and the scope of venomous animal groups whose venom biochemistry has been examined is ever-expanding, having recently grown to encompass such animals as the platypus [ 4 ], centipedes [ 5 ], assassin bugs [ 6 , 7 ], and polychaete worms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the venom systems of arachnids, snakes, and marine cone snails, among others, have revealed that venoms are typically complex composites of peptides, small molecules, pore-forming proteins, and enzymes that target the nervous and/or cardiovascular system to incapacitate prey or deter predators. Venom has evolved multiple times among animals [ 1 , 2 , 3 ], and the scope of venomous animal groups whose venom biochemistry has been examined is ever-expanding, having recently grown to encompass such animals as the platypus [ 4 ], centipedes [ 5 ], assassin bugs [ 6 , 7 ], and polychaete worms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many lepidopteran species from different families can produce venoms, suggesting that toxin genes evolved independently many times in Lepidoptera evolution. Convergent evolution is a fundamental process in animal venom evolution [ 3 , 113 ]. Our findings indicate that some toxin classes have been repeatedly recruited into the venom of Lepidoptera, particularly serine protease, protease inhibitor, phospholipase A2, and lectin, as reported in P .…”
Section: Discussionmentioning
confidence: 99%
“…Animal venoms are complex secretions consisting mainly of bioactive proteins and peptides ( Fry et al, 2009 ; Casewell et al, 2013 ) that primarily serve as a chemical means of protection and subduing prey. Venom has evolved independently throughout the animal kingdom ( Casewell et al, 2013 ; Suranse et al, 2018 ); consequently, it is present in all major animal lineages ( Holford et al, 2018 ). All of the 1,500 extant scorpion species are venomous.…”
Section: A Brief Overview Of Venomous Scorpions With Particular Reference To Indian Red Scorpionmentioning
confidence: 99%